A two-part dynamic pricing policy for household electricity consumption scheduling with minimized expenditure - Mitra, Krishnendranath; Dutta, Goutam (International journal of electrical power & energy systems, 2018)
•Mixed integer, non-linear cost minimizing scheduling model with logical constraints.•The model includes power grid, in-house renewable energy and battery.•Real-time, two-part pricing based on forecasted grid demand and planned consumption.•The consumer gets a unique price using a piecewise linear price function.•A price range is provided by supplier instead of discrete price points. In this paper we propose an optimization model for scheduling electrical appliances for an individual household. Here, customers are offered dynamic prices which are a function of that household’s planned consumption and forecasted grid load. We consider a grid connected system with a battery and an in-house renewable energy generator in the proposed scheduling model. This model minimizes the customer’s electricity bill subject to different constraints. We analyze our model with various pricing policies, price ranges and appliance operation windows. We find that the expenditure of the consumer decreases considerably in our model when shifting from flat prices to dynamic prices based on the forecasted grid load and the consumer’s individual planned consumption. Considerable expenditure reduction and individual load flattening is achieved with the use of a battery and an in-house renewable energy generator. Also, larger the price range, higher is the load flattening and lower is the expenditure. We show that our proposed pricing policy is beneficial to both consumers and suppliers.